The impact of oscillometric blood pressure measurement on pain response in preterm neonates - Reddy, Yerramada Narsimha; Shamakrishna, Surabhi H.; Venkataramaiah, Venkatesh Murthy Dammaningala; Gupta, Rajanish Kanduri Vishwanatha (International Journal of Contemporary Pediatrics, 2026)
Background: Preterm neonates admitted to neonatal intensive care unit (NICU) are subjected to numerous painful and potentially noxious procedures. Oscillometric blood pressure (BP) measurement, although classified as non-invasive, involves repeated application and inflation of a cuff on a fragile limb, and may elicit a significant pain response in this vulnerable population. The extent of this pain in preterm neonates, particularly in the Indian context, remains inadequately studied. Aim was to assess the pain response to non-invasive oscillometric BP measurement in preterm neonates using the premature infant pain profile-revised (PIPP-R). Methods: A prospective observational study was conducted at the NICU of Rajarajeswari Medical College and Hospital, Bangalore, enrolling 50 preterm neonates (gestational age <36 weeks and post menstrual age <37 weeks). PIPP-R scores were recorded at three timepoints: baseline (T1), during BP measurement (T2), and 10 minutes after the procedure (T3). For within-group analysis, the Friedman test with post-hoc Wilcoxon signed-rank tests (Bonferroni correction) was used. Clinical characteristics were compared between neonates with pain and without pain using Mann-Whitney U and chi-square tests. Results: Median PIPP-R scores were significantly higher during BP measurement (T2) compared to baseline (T1) and 10 minutes post-procedure (T3) (χ²=38.99, p<0.001). Out of 50 neonates, forty two percent of neonates (n=21) had pain during the procedure. Neonates with pain had significantly lower gestational age, birth weight, post menstrual age. (p<0.05). Conclusions: Oscillometric BP measurement causes clinically significant pain in a substantial proportion of preterm neonates, particularly those with lower gestational age and birth weight. Individualized monitoring strategies and non-pharmacological pain management should be considered in this population.